The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s40795-020-00401-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of infant and young complementary feeding practices among children 6–23 months of age in urban Pakistan: a multicenter longitudinal study

Abstract: Background Suboptimal feeding practices have a negative impact on children’s health and growth in the first 2 years of life and increase their risk of undernutrition, morbidity, and mortality. The aim of the study was to assess the factors that influence infant and young child feeding practices among urban mothers in a hospital setting at Karachi, Pakistan. Methods A longitudinal multi-center cohort study was conducted in four countries, MULTICENTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Unavailability and unaffordability, as well as insufficient maternal education, were identified as some of the main factors limiting consumption of animal-source foods and nutrient-dense foods in general among infants and young children in the two regions (2,10,41,42). Indeed, while some foods of animal origin, such as liver, eggs and dairy, may be more available and affordable than others (particularly in terms of cost per nutrients provided), efforts to increase access to and knowledge around ASFs in South and Southeast Asia are still needed (43).…”
Section: Discussionmentioning
confidence: 99%
“…Unavailability and unaffordability, as well as insufficient maternal education, were identified as some of the main factors limiting consumption of animal-source foods and nutrient-dense foods in general among infants and young children in the two regions (2,10,41,42). Indeed, while some foods of animal origin, such as liver, eggs and dairy, may be more available and affordable than others (particularly in terms of cost per nutrients provided), efforts to increase access to and knowledge around ASFs in South and Southeast Asia are still needed (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Lebanese study conducted in 2017 showed that the proportion of exclusively breastfed infants declined from 40% at age 2 months to 2% at 4–6 months [ 62 ]. Many other EMR countries showed similar trend such as Jordan (at birth: 51%, at 1 month: 47%, at 6 months: 33%) [ 56 ], Iran (at discharge:74.3%, at 6 months: 28%) [ 46 ], Pakistan (at 3 months: 74.4%, at 6 months: 30.2%) [ 72 ], Qatar (at 1–3 months: 40%, at 4–6 months: 20%) [ 19 ], Saudi Arabia (at birth: 88.6%, at 1 month: 49%, at 2 months: 36.1%, at 4 months: 20.5%, at 6 months: 10.2%) [ 80 ] and United Arab Emirates (at 0–3.9 months: 45%, at 0–6 months: 37%, at 4–5.9 month: 26%) [ 16 ]. Additionally, over time, some countries in the region have seen a decline in the prevalence of exclusive breastfeeding.…”
Section: Resultsmentioning
confidence: 97%
“…The lowest rates were seen for Kuwait (12%) [ 60 ], Saudi Arabia (11.1%) [ 80 ] and United Arab Emirates (1%) [ 16 ]. However, the highest rates were reported from Afghanistan (73.8%) [ 37 ], Iran (70.5%) [ 47 , 50 ], Sudan (68.2%) [ 37 , 85 , 86 , 87 ], Pakistan (65.1%) [ 23 , 37 , 72 , 73 , 74 ] and Oman (64.1%) [ 29 , 70 , 71 ]. The prevalence of continued breastfeeding decreased the most at 2 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The rst 2 years of life are crucial as during this period, the body lays the foundation for the future growth and development of a child. Any nutritional de ciencies during this time can be manifested in the form of impaired cognitive development, and physical growth (29,30) compromised educational achievement, and ultimately low economic productivity later in life (31). Furthermore, the role of breastfeeding in boosting child immunity was evident and the weaknesses of eating habits decreased child immunity and considered as an entry point to COVID-19 (32) and as a trigger for increasing phobia (33) Optimization of breastfeeding practices could reduce high mortality rates in children younger than 5 years.…”
Section: Discussionmentioning
confidence: 99%